Order Fulfillment pada Taksi Online dengan Mempertimbangkan Prioritas Penumpang Menggunakan Metode Recency, Frequency dan Monetary - Viona Angelica; Andreas Handojo; Tanti Octavia (Universitas Kristen Petra, 2022)
Along with the development of technology in Indonesia, online taxi companies are one of the fields that are starting to be developed. Just like other companies, online taxi companies are looking for profits, to achieve it, they need to maintain good relations with their passengers. That can be achieved by improving service to loyal passengers. In this study, factors will be applied to improve service to loyal passengers and drivers such as rating, number of trips, driver’s RFM score and passenger’s RFM score. The method used to segment drivers and passengers is RFM prioritization and Filtered RFM prioritization. The method used to pair the driver and passengers is the Hungarian method. This study shows that by adding additional factors such as driver and passenger RFM scores, driver ratings, and the number of trip drivers accompanied by a passenger pick-up time limit, don’t change the assign time, waiting time, and pickup time of passenger but can prioritize passengers and drivers according to those factors. In addition, internet speed also has a huge influence on website-based order fulfillment simulations.